Mentorship Gereja dalam Membentuk Karakter Remaja di BNKP Jemaat Hiliomasio Medan - Yunardi Kristian Zega (Vox Dei: Jurnal Teologi dan Pastoral, 2021)
The times are changing rapidly, along with the many technologies created by humans. On the one hand, technology brings many positive influences to facilitate human life. But on the other hand, technology can also have negative consequences for people who use it incorrectly. One of the negative impacts of today's technological developments, can be seen from the increasing number of delinquency cases among adolescents. Therefore, many parents are confused and don't know what to do, due to the influence of digital technology that has damaged the character of teenagers, especially for teenagers in BNKP Congregation Hiliomasio Medan. To solve this problem, researchers used qualitative research using a descriptive approach method. Where researchers go directly into the field so that they can find accurate and accountable data. The results of this research include: 1) the implementation of church mentorship on Christian Religious Education in the Family still needs to be further improved, 2) the church needs to give more serious attention to the teaching of Christian Religious Education for all congregations, and 3) implementation Christian Religious Education in the Family towards efforts to shape the character of adolescents in the digital era, still looks very lacking.